Competence as a determinant of employee performance work motivation and career development as triggers - Tajudin Tajudin; Syaechurodji Syaechurodji; Abdul Wahid Alfarizi; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
Every agency wants all its employees to be able to contribute, namely in the form of the best work performance as expected by the agency, which in turn will enable the agency to achieve its goals. To achieve this goal, many factors influence, including competence, work motivation, and career development. Agencies must be able to create conditions that can motivate employees to work well. This study aims to analyze the factors that can explore improving employee performance in existing models; high employee competence, high work motivation, and appropriate career development will be able to improve employee performance. This research uses associative quantitative methods with a survey approach. The object of this research is the Serang Regency Regional Civil Service Agency, with a sample of 188 respondents. The results of this study indicate that competence has a significant effect on employee performance. Competence has a considerable impact on work motivation. Competence has a substantial effect on career development. Work motivation is having a significant impact on employee performance. Career development has a significant effect on employee performance. Work motivation and career development can mediate the effect of competence on employee performance. This research is expected to make a theoretical contribution to the literature in this context.